2018
DOI: 10.1002/nau.23507
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a mobile application‐based treatment for urinary incontinence in adult women: Design of a mixed‐methods randomized controlled trial in a primary care setting

Abstract: Aims:We aim to assess whether a purpose-developed mobile application (app) is non-inferior regarding effectiveness and cost-effective when used to treat women with urinary incontinence (UI), as compared to care as usual in Dutch primary care. Additionally, we will explore the expectations and experiences of patients and care providers regarding app usage. Methods: A mixed-methods study will be performed, combining a pragmatic, randomized-controlled, non-inferiority trial with an extensive process evaluation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 23 publications
(42 reference statements)
0
32
0
Order By: Relevance
“…The complete study protocol was published previously. 6 After trial commencement, an amendment to the protocol added a process evaluation method and changes to recruit participants from the general population because of a low accrual rate. 7 We followed the Consolidated Standards of Reporting Trials (CONSORT) guideline and the relevant extensions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete study protocol was published previously. 6 After trial commencement, an amendment to the protocol added a process evaluation method and changes to recruit participants from the general population because of a low accrual rate. 7 We followed the Consolidated Standards of Reporting Trials (CONSORT) guideline and the relevant extensions.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 We reported details on the development and content of this app previously. 6 Participants received a personal account and instructions to download and install the app on their smartphone or tablet. The research team provided technical support only.…”
Section: App-based Treatmentmentioning
confidence: 99%
“…Thematic analyses provide subthemes describing these experiences and preferences, as they are closely interwoven [10]. We conducted semistructured in-person interviews as part of the URinControl study, a mixed-methods study consisting of a randomized controlled trial (RCT) with extensive process evaluation to assess the expectations and experiences of patients and care providers regarding app-based treatment of UI in women [11]. The relevant medical ethics committee approved this study (M17.207954), and the COREQ guideline was followed in this report [12].…”
Section: Methodsmentioning
confidence: 99%
“…The development of the URinControl app has been described elsewhere [11]. It provides step-by-step advice for treating stress UI, urgency UI, and mixed UI in a patient-friendly format based on the guidelines for treating female UI in primary care [13] ( Figure 1).…”
Section: The Urincontrol Appmentioning
confidence: 99%
“…This embedded and comprehensive theoretically informed mixed-methods process evaluation is unique to the trials conducted so far in the field of PFMT. To the best of our knowledge, only one trial 11 has reported a process evaluation and this was a single-method (qualitative) approach; one new trial is planning a mixedmethod evaluation 58 and an earlier trial reported plans for a process evaluation. 59 The multiple data sources in the OPAL trial bring a richness to our understanding of trial processes and experiences of the therapists…”
Section: Resultsmentioning
confidence: 99%